The effectiveness of river water treatment plant in improving water quality in Sungai Kemensah - Zainor Rahim, Aliff Ezwan (2015)
The government of Malaysia has spent huge amount of money to improve the river quality under the Malaysian Economic Transformation Program (ETP) with the intention of bringing river back to life and to ‘bring’ people towards the river. The main purpose of the treatment plant is basically to improve the river water from polluted state to the state where the water can be contacted with human skin without any harm that is Class II Water Quality Index (WQI). This study is conducted to determine the effectiveness of River Treatment Plant (RWTP) that are implemented in Sungai Kemensah in year 2012. The River Water Treatment Plant is technically similar to the sewerage treatment plant but it has been further enhanced to suit the river water condition where it consist of biomedia filter, extended aeration and proper aeration system. The study involved grab sampling which were conducted three times; pre, during and post project stage. The idea of taking these samples in phases was to determine the difference or the improvement made by the RWTP once has it has been fully operated towards the water quality. The samples were then analysed using the WQI formula to determine its class. Based on the final findings, it found that the concentration of dissolve oxygen is somehow maintained but both Biochemical Oxygen Demand (BOD) and Ammoniacal Nitrogen (AN) decreased tremendously from 19.20 mg/L to 2.33 mg/l and 5.31mg/l to 0 mg/l respectively. It can be concluded that the RWTP is proven to be effectively improving the water quality from polluted to safe state.